2016
DOI: 10.4172/2329-6607.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the New P2Y12 Receptor Inhibitors on Mortality in STElevation Myocardial Infarction Patients with Cardiogenic Shock and / or After Cardiopulmonary Resuscitation Undergoing Percutaneous Coronary Intervention

Abstract: IntroductionST-Elevation Myocardial Infarction (STEMI) represents a highly pro-thrombotic state with platelets being greatly activated [1,2]. The early and strong platelet inhibition seems to be of paramount importance in patients with STEMI undergoing Percutaneous Coronary Intervention (PCI) [3]. Newer P2Y12 receptor inhibitors prasugrel and ticagrelor (newer P2Y12) exhibit more rapid, potent, and consistent platelet inhibition than clopidogrel and reduce the risk for ischemic cardiovascular complications [4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The percentage of patients receiving a combination of P2Y12 in our analysis (9.7%) was comparable to the pooled analysis of two randomized controlled prospective trials (13.1%) ( 2 ). Results of previous analyzes are inconclusive and sometimes contradictory ( 2 , 3 , 9 , 11 , 19 21 ). Retrospective analyzes and pooled data showed superiority of potent P2Y12 ( 3 , 12 , 9 ), whereas prospective and some retrospective studies showed no difference in survival between P2Y12 ( 2 , 11 , 19 21 ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The percentage of patients receiving a combination of P2Y12 in our analysis (9.7%) was comparable to the pooled analysis of two randomized controlled prospective trials (13.1%) ( 2 ). Results of previous analyzes are inconclusive and sometimes contradictory ( 2 , 3 , 9 , 11 , 19 21 ). Retrospective analyzes and pooled data showed superiority of potent P2Y12 ( 3 , 12 , 9 ), whereas prospective and some retrospective studies showed no difference in survival between P2Y12 ( 2 , 11 , 19 21 ).…”
Section: Discussionmentioning
confidence: 97%
“…In patients with CS, multiple challenges with antiplatelet action remain ( 9 ). The antiplatelet effect of orally administered drugs is delayed by gastroparesis, delayed intestinal absorption, and slower metabolism of the drugs due to compromised hemodynamics in cardiogenic shock, and after morphine administration ( 3 , 5 7 , 10 ). In addition, oral administration of the drugs may be problematic ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations